On evaluation codes coming from a tower of function fields. (November 2018) - Carvalho, Cícero; Chara, María; Quoos, Luciane
Abstract: In this work we present the construction of evaluation codes defined from data coming from a tower of function fields. We use tools from Gröbner basis theory to calculate the dimension and find a lower bound for the minimum distance of these codes.